Illuminating the impact of reproductive extracellular vesicles: modeling maternal signals during preimplantation embryo development - Menjivar, Nico Graham, author; Tesfaye, Dawit, advisor; Krisher, Rebecca L., advisor; Chicco, Adam, committee member; Hollinshead, Fiona K., committee member (Colorado State University. Libraries, 2024)
Pre-implantation embryo development is a complex process beginning around the time of gametic syngamy, the process of two gametes fusing to create a zygote (the first cell of a new organism). Passively transient through the oviduct, the presumptive zygote is then characterized by a series of timely cleavage divisions, activation of the embryonic genome, compaction (morula formation), cavitation (blastocyst formation), and summing in hatching from the encapsulated zona pellucida and implantation to the uterine wall. Unfortunately, the current IVF system that occurs ex vivo, completely bypasses the critical maternal-embryonic crosstalk that would inevitably persist during the primitive stages of pre-implantation development. It is thought that the low yield of developed embryos in vitro, is in part due to the failed ability to recapitulate a suitable system that mimics the maternal environment, shunting early cleavage stage embryos for failure. However, the reservations regarding maternal signals secreted to developing embryos, the reproductively inaccessible nature of the organs, and suboptimal in vitro systems to study replicate in vivo function has limited our complex understanding of these stages. In this dissertation, I aimed to interrogate multiple aspects of preimplantation embryo development, under the primary premise of modeling maternal signal during the pre-implantation period. Utilizing the intrinsic interest in the growing field of extracellular vesicle (EV) research and their significance in intercellular signaling, particularly their communicative role in selective biological information transfer, my first exertion was developing a source of EVs from in vitro cultured granulosa cells for use during IVM (necessitating maternal signals amid the follicle microenvironment). Through the analysis of this dataset (in combination with Gebremedhn et al. 2020) together with immunofluorescence and functional experiments, we characterized diverging miRNA profiles of EVs secreted by granulosa cells subjected to polarizing thermal conditions, that are abundantly up taken by COCs and modulate key developmental events that safeguard developing embryos exposed to conditions of stress. Next, I built upon this work by generating a functional 3D organoid model to study the cellular and extracellular response of the oviduct using a multi-omics approach. Using this atlas as a guide, I characterized the functional undertakings of the oviduct during applied levels of heat stress and found its crucial role in altering the metabolic activity of maternal tissues, which likely in part functionally augment developing embryos and assume failure. Given the functional applicability of reproductive EVs acting as maternal cues, I established this suitable model as a mechanism to generate physiologically relevant EVs (in vivo-like) to offset applied stress during the initial stages of development. These EVs secreted from 3D cultured oviductal organoids were then compared with those secreted from 2D OECs and from in vivo oviductal fluid (miRNAs), and used in an IVC setting, highlighting functional maternal—embryonic crosstalk. Altogether, this dissertation highlights key functional aspects of reproductive extracellular vesicles from both the follicular microenvironment and the oviduct, highlighting the novel and incredible power of suitable in vitro systems to propagate mechanisms to understand maternal signal absent in the current in vitro systems, beginning to illuminate the 'black box' of EVs in embryo development.
Keywords: extracellular vesicles; oocytes; embryos; organoids; microRNAs